2017
DOI: 10.3390/rs9100982
|View full text |Cite
|
Sign up to set email alerts
|

Wuhan Surface Subsidence Analysis in 2015–2016 Based on Sentinel-1A Data by SBAS-InSAR

Abstract: Abstract:The Terrain Observation with Progressive Scans (TOPS) acquisition mode of Sentinel-1A provides a wide coverage per acquisition and features a repeat cycle of 12 days, making this acquisition mode attractive for surface subsidence monitoring. A few studies have analyzed wide-coverage surface subsidence of Wuhan based on Sentinel-1A data. In this study, we investigated wide-area surface subsidence characteristics in Wuhan using 15 Sentinel-1A TOPS Synthetic Aperture Radar (SAR) images acquired from 11 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(98 citation statements)
references
References 50 publications
(54 reference statements)
2
96
0
Order By: Relevance
“…This technique overcomes the low coherence of some interferograms induced by single super-master images and reduces the requirement of the quantity of SAR images with respect to PS-InSAR [29]. SBAS-InSAR is widely applied in land subsidence detection [26,27,31], and is based on the following equations [25]:…”
Section: Basic Theory Of Sbas-insarmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique overcomes the low coherence of some interferograms induced by single super-master images and reduces the requirement of the quantity of SAR images with respect to PS-InSAR [29]. SBAS-InSAR is widely applied in land subsidence detection [26,27,31], and is based on the following equations [25]:…”
Section: Basic Theory Of Sbas-insarmentioning
confidence: 99%
“…More specifically, a permanent scatterers InSAR (PS-InSAR) method proposed by Ferretti et al and a small baseline subset InSAR (SBAS-InSAR) method introduced by Berardino et al have been widely used in related fields with millimetric accuracy [23][24][25]. Zhang and Zhou analyzed Wuhan land subsidence using SBAS-InSAR, and observed four major subsidence zones affected by urban construction and industrial development [26,27]. Chaussard et al calculated land subsidence in Mexican and Indonesian cities using the SBAS-InSAR method, and found that land subsidence was directly related to the overexploitation of groundwater [2,28].…”
mentioning
confidence: 99%
“…it is often caused by consolidation and compression of underground unconsolidated strata . Surface subsidence is also one of the major disasters that can cause serious damage to infrastructures, tunnels, roads, bridges, and buildings, which made a huge impact to the safety of the cities Zhou et al, 2017). With its long history of subsidence, way back to the 1930s (Fan, 2006), Wuhan still continuously suffers from this hazards due to the fast urban development and subway constructions (Goethals, 2011).Compared to single-point-measurement methods such as ground leveling (Baldi et al, 2009;Poland et al, 2006) or Global Navigation Satellite System (GNSS) (Carminati et al, 2002;Psimoulis et al, 2007), Differential Interferometric Synthetic Aperture Radar (D-InSAR) has been developed to measure relatively slow surface motion between two SAR image acquisitions (Avallone et al, 1999) and it has been used widely for subsidence monitoring (Cigna et al, 2012;Solari et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the emergence of synthetic aperture radar (SAR) technique provides an effective method for effectively monitoring the urban overall surface subsidence. Differential Interferometric Synthetic Aperture Radar (DInSAR) overcomes the shortcomings of traditional monitoring methods such as low spatial resolution and high cost (Zhou et al, 2017), and has been successfully applied to seismic deformation detection (Li et al, 2011), landslides (Calò et al, 2014), and urban surface subsidence analysis (Guo et al, 2016). However, DInSAR is susceptible to atmospheric delay, which is difficult to obtain high precision deformation information.…”
Section: Introductionmentioning
confidence: 99%